Analysis of Dry Food Ingredients Procurement Model Based on EOQ (Economic Order Quantity) at the Nutritional Installation - Elsi Rahmini; Ermi Girsang; Santy Deasy Siregar (Postgraduate, University of Mataram, 2023)
Nutritional problems in hospitals are assessed according to individual conditions which directly or indirectly affect the healing process. The trend of increasing cases of nutrition-related diseases in all vulnerable groups, from pregnant women, babies, children, teenagers, to the elderly, requires special nutritional management. Therefore, quality food/nutrition services or administration are needed to achieve and maintain optimal nutritional status and accelerate healing. This research is viewed from the intervention carried out on the research object, which is pre-experimental research using descriptive evaluative methods, observational approaches and interviews. The results of this research show that the ratio of procurement of dry food ingredients at the Nutritional Installation of RSUP H. Adam Malik Medan is efficient. It is proven that the TOR value obtained is 1.79, which means that the stock of dry food ingredients is used and updated properly, so that the supply is sufficient to meet patient needs and prevent excessive overstocking